A nanocomposite material, fire-proof pre-reaction liquid, and preparation method and application thereof
By using nanocomposite materials and special processes with a ‘super-shaped multi-layer core-shell structure and multiple cross-linkable, the existing flame-retardant fire-resistant transparent coating prereaction solution has solved the problems of poor UV radiation resistance and other insufficient performance, and achieved a high-performance fire-resistant layer material suitable for outdoor and low-temperature environments.
Patent Information
- Application Number
- CN202411499256.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing flame-retardant fire-resistant transparent coating prereaction has poor UV radiation resistance, needs frequent application, and cannot meet long-term requirements when used outdoors. It also has poor solvent resistance, hardness, low temperature resistance and impact resistance, which affects the actual fire resistance and service life.
Using nanocomposite materials with a multi-layer core-shell structure with a "saccharia" shape and can be cross-linked multiple times, the gradation blending technology and semi-continuous self-assembly technology are used to optimize the gradation effect of nanosilicon dioxide particles, reduce the system viscosity, and introduce low-temperature induced accumulation technology and gradient heating reaction in the fire-proof prereaction liquid to form a synergistic effect and eliminate the bubbles in the composite fire-proof glass interlayer.
It realizes high performance of fire-resistant layer materials, has excellent performance of low temperature resistance, deformation resistance and fire integrity, and has ultraviolet radiation resistance time of more than 3,000 hours. It is suitable for outdoor environments and maintains good performance under low temperature conditions.
Smart Images

Figure CN119371689B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of glass safety, and in particular to an organic / inorganic nanomaterial having a "roxburghii"-shaped multi-layer core-shell structure and capable of multiple cross-linking, a fireproof pre-reaction liquid, and a preparation method and application thereof. Background Art
[0002] As urbanization progresses at an increasingly rapid pace, the building windows of houses are becoming larger and larger. Elegant, beautiful, and functional glass components are gradually gaining favor among designers at home and abroad, which directly leads to the rapid development of various types of safety glass and special glass in the architectural glass industry. Architectural glass has gradually developed from being a simple lighting and decorative material to having multiple functions such as light control, room temperature regulation, noise reduction, and improvement of living environment. Special coatings have gradually developed from being a simple anti-corrosion and decorative material to having multiple functions such as flame retardancy, heat insulation, wear resistance, damping, and noise reduction.
[0003] As a safe coating, flame retardant fireproof transparent coating pre-reaction liquid not only has some properties of ordinary coatings, but also has the properties of controlling the spread of fire and heat insulation, which provides valuable rescue time for effective rescue in the event of a fire, minimizes the loss of personnel, property and vehicles, and reduces the destructive power of fire to a minimum. Fireproof glass can be formed when coated on the surface of glass. In addition to having some properties of ordinary glass, coated fireproof glass can also protect escape and rescue personnel from heat radiation damage. Poor resistance to ultraviolet radiation is one of the main factors restricting the application of flame retardant coatings. Therefore, developing high-performance flame retardant fireproof transparent coating pre-reaction liquid with excellent resistance to ultraviolet radiation and expanding the application area of the product is an important direction for the industrialization development of special coatings.
[0004] At present, the work done in China on flame-retardant fireproof transparent coating pre-reaction liquid for glass is at the basic research stage. The existing flame-retardant fireproof transparent coating pre-reaction liquid has poor ultraviolet radiation resistance and needs to be applied frequently and regularly, with a large amount of fireproof coating. At the same time, most products will crack and fall off from the glass surface under long-term outdoor ultraviolet radiation, and cannot meet the requirements for long-term outdoor use in the rainy southern regions; the existing flame-retardant coating also has poor solvent resistance, hardness, low temperature resistance, and impact resistance, which reduces the actual fireproof effect of the fireproof layer and seriously affects the use effect and service life of the flame-retardant fireproof transparent coating pre-reaction liquid. Summary of the invention
[0005] The main purpose of the present invention is to provide a nano-composite material with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking, a fire-proof pre-reaction liquid and a preparation method and application thereof, which overcomes the disadvantages of the fire-proof layer material in the prior art that cannot meet the ultraviolet test, and avoids the shortcomings of cracking of the fire-proof layer, mismatch between impact resistance and hardness, and poor water resistance.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0007] A nanocomposite material comprises organic nanoparticles and organic / inorganic hybrid nanoparticles, wherein the organic nanoparticles and the organic / inorganic hybrid nanoparticles both comprise a flexible core layer, a shell layer and a reinforcing transition layer, wherein the reinforcing transition layer is arranged between the flexible core layer and the shell layer; the surface of the shell layer of the organic nanoparticles is grafted with linear ammonium polyphosphate, and the surface of the shell layer of the organic / inorganic hybrid nanoparticles is grafted with linear poly(glycidyl methacrylate); the flexible core layer is polyacrylamide latex particles, the reinforcing transition layer is a polymer layer containing melamine formaldehyde material with a cross-linked network structure, the shell layer of the organic nanoparticles is a polymer layer containing a phosphorus-containing polymer, and the shell layer of the organic / inorganic hybrid nanoparticles is a polymer layer containing an epoxy polymer; the polymer in the shell layer of the organic nanoparticles and the polymer in the shell layer of the organic / inorganic hybrid nanoparticles both contain at least one polymer that can form an interpenetrating network structure with cellulose, and in the present invention, the linear poly(glycidyl methacrylate) and the linear ammonium polyphosphate can both form an interpenetrating network structure with cellulose;
[0008] The material composed of organic nanoparticles is made of the following components: 7 to 26 parts by weight of a third mixed solution and 41 to 302 parts by weight of a second polymer template emulsion; the third mixed solution is made of 5 to 15 parts by weight of ammonium polyphosphate, 0.1 to 1 parts by weight of ethanol and 2 to 10 parts by weight of deionized water; the second polymer template emulsion is made of 0.1 to 19 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 0.003 to 0.03 parts by weight of an initiator, and 26 to 243 parts by weight of a first polymer template emulsion; the second mixed solution is made of 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid, 0.1 to 1 parts of 3-butene-1-amine and 0.01 to 0.0 The first polymer template emulsion is made of 0.4-80 weight parts of the first mixed solution, 6-12 weight parts of deionized water, 0.005-1 weight part of initiator and 20-150 weight parts of polyacrylamide emulsion with a particle size of 40nm-200nm and a solid content of 15wt%-55wt%; the first mixed solution is made of 0.1-20 weight parts of butyl acrylate, 0.1-20 weight parts of melamine, 0.1-20 weight parts of styrene, 0.01-0.03 weight parts of divinyl sulfone, 0.05-0.2 weight parts of ammonia water with a concentration of 20wt%, 0.1-20 weight parts of 2,4-methyl-3-cyclohexene carboxaldehyde and 0.002-0.08 weight parts of reactive emulsifier;
[0009] The material composed of organic / inorganic hybrid nanoparticles is made of the following components: 10 to 25 parts by weight of a fifth mixed solution and 51 to 327 parts by weight of a fourth polymer template emulsion; the fifth mixed solution is made by mixing 5 to 15 parts by weight of glycidyl methacrylate, 0.01 to 0.2 parts by weight of an initiator and 5 to 10 parts by weight of deionized water; the fourth polymer template emulsion is made by mixing 0.1 to 18 parts by weight of the fourth mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a hydrophilic silica dispersion with double bonds on the surface, 0.003 to 0.03 parts by weight of an initiator and 26 to 243 parts by weight of a first polymer template emulsion; the fourth mixed solution is made by mixing 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid and 0.01 to 0.02 parts by weight of a reactive emulsifier; the first polymer template emulsion is made by mixing 0.4 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of a The first mixed solution is prepared by mixing 0.1-20 parts by weight of butyl acrylate, 0.1-20 parts by weight of melamine, 0.1-20 parts by weight of styrene, 0.01-0.03 parts by weight of divinyl sulfone, 0.05-0.2 parts by weight of 20wt% ammonia water, 0.1-20 parts by weight of tantalum, and 0.1-20 parts by weight of tantalum. The invention discloses a method for preparing a silica dispersion liquid comprising a silica seed solution and a silica slurry. The method comprises mixing 2,4-methyl-3-cyclohexene formaldehyde in parts by weight and a reactive emulsifier in parts by weight. The hydrophilic silica dispersion liquid with double bonds on the surface is prepared from 10 to 25 parts by weight of a silica seed solution, 0.1 to 1 parts by weight of an alkenyl silane coupling agent and 0.001 to 0.02 parts by weight of ethanol. The silica seed solution is prepared from 2 to 3 parts by weight of tetraethyl orthosilicate, 0.02 to 0.04 parts by weight of concentrated ammonia water with a concentration of 25wt% and 8 to 22 parts of deionized water.
[0010] In the nano composite material, the polymerization degree of the polyacrylamide particles in the polyacrylamide emulsion is 10000-100000, the particle size is 40nm-200nm, and the particle size distribution is a single peak narrow distribution.
[0011] In the nanocomposite material, the alkenyl silane coupling agent is one or more of vinyl tert-butyl triperoxide silane, vinyl triethoxy silane, butadienyl triethoxy silane, vinyl trimethoxy silane, isobutylenyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane.
[0012] In the nanocomposite material, the initiator is one or both of a thermal initiator and a redox initiator.
[0013] In the above nanocomposite material, the emulsifier is a reactive emulsifier.
[0014] The method for preparing the above-mentioned nanocomposite material comprises the following steps:
[0015] S11) preparing a silicon dioxide seed solution: mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm;
[0016] S12) preparing a silica dispersion with double bonds on the surface: placing a silica seed solution, an alkenyl silane coupling agent and ethanol in a ratio of 10 to 25: 0.1 to 1: 0.001 to 0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes, placing the mixture in a three-necked flask, and then placing the three-necked flask in a water bath at 70° C. to 90° C., stirring and dispersing at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooling to 20° C. to obtain a silica dispersion with double bonds on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11);
[0017] S13) preparing a first polymer template emulsion, the specific steps are as follows:
[0018] S13-1) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier in weight proportions of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution;
[0019] S13-2) By means of starvation polymerization, 0.4 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure;
[0020] S14) preparing an emulsion containing organic nanoparticles, the specific steps are as follows:
[0021] S14-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid, 3-butene-1-amine and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.1-1:0.01-0.02 to prepare a second mixed solution;
[0022] S14-2) preparing a second polymer template emulsion: by means of starvation polymerization, 0.1 to 19 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 243 parts by weight of the first polymer template emulsion at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) material containing an amino group is coated on the surface of the polyacrylamide latex particles to obtain a second polymer template emulsion having a multilayer core-shell structure;
[0023] S14-3) preparing a third mixed solution: mixing ammonium polyphosphate, ethanol and deionized water in a weight ratio of 5-15:0.5-1:2-10 to prepare a third mixed solution;
[0024] S14-4) preparing an emulsion containing organic nanoparticles: by means of an ion exchange reaction, 7 to 26 parts by weight of the third mixed solution are added dropwise to 41 to 302 parts by weight of the second polymer template emulsion at a constant speed at a temperature of 30 to 40° C., stirred at a stirring speed of less than 80 r / min, and refluxed and condensed at this temperature for 4 hours to form a polymer with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles, thereby obtaining an emulsion containing organic nanoparticles;
[0025] S15) preparing an emulsion containing organic / inorganic hybrid nanoparticles, the specific steps are as follows:
[0026] S15-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.01-0.02 to prepare a fourth mixed solution;
[0027] S15-2) preparing a third polymer template emulsion: by means of a starvation polymerization method, at a temperature of 60 to 65° C., 0.1 to 18 parts by weight of the fourth mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having double bonds on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of the first polymer template emulsion at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silica particles having a particle size of 20 nm to 30 nm and having double bonds is coated on the surface of the polyacrylamide latex particles, thereby obtaining a third polymer template emulsion having a bayberry-like multilayer core-shell structure;
[0028] S15-3) preparing a fifth mixed solution: preparing a fifth mixed solution by mixing glycidyl methacrylate, an initiator and deionized water in a weight ratio of 5-15:0.01-0.2:5-10;
[0029] S15-4) preparing an emulsion containing organic / inorganic hybrid nanoparticles: adding 10 to 25 parts by weight of the fifth mixed solution to 51 to 327 parts by weight of the third polymer template emulsion at a constant speed at a temperature of 60 to 65° C., stirring at a stirring speed of less than 80 r / min, and reflux condensing for 3 hours at this temperature to form a second polymer with linear poly(glycidyl methacrylate) as a branch on the surface of the latex particles, thereby obtaining an emulsion containing organic / inorganic hybrid nanoparticles;
[0030] S16) mixing the emulsion containing organic nanoparticles and the emulsion containing organic / inorganic hybrid nanoparticles to obtain a nanocomposite material.
[0031] A fireproof pre-reaction liquid comprises at least the following components: 48 to 328 parts by weight of organic nanoparticles, 61 to 352 parts by weight of organic / inorganic hybrid nanoparticles, 0.5 to 4 parts by weight of cellulose solvent, 0.5 to 2.5 parts by weight of catalyst and 10 to 30 parts by weight of deionized water; the organic nanoparticles are the above-mentioned organic nanoparticles, and the organic / inorganic hybrid nanoparticles are the above-mentioned organic / inorganic hybrid nanoparticles.
[0032] The above-mentioned fire-proof pre-reaction liquid also includes: 1 to 5 parts by weight of a carbonizing agent, 0.001 to 0.05 parts by weight of a defoaming agent and 0.1 to 1 parts by weight of a rheological additive; the carbonizing agent is compounded by pentaerythritol and one or more of sucrose, fructose, glucose and maltose; the rheological additive is one or more of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the antifreeze plasticizer is one or more of ethylene glycol, glycerol and 1,4-butanediol; the cellulose solvent is one or both of dipropylene glycol methyl ether and N-methylmorpholine oxide; the catalyst is compounded by a dilute hydrochloric acid solution with a mass concentration less than or equal to 20wt% and one or both of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite; the defoaming agent is one or both of a polysiloxane defoaming agent and a polyether defoaming agent.
[0033] The method for preparing the fire-proof pre-reaction liquid comprises the following steps:
[0034] Step S21), a carbonizing agent, a rheological additive, and deionized water are mixed in a weight ratio of 1-5:0.1-1:10-25, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and allowed to stand for 12 hours to obtain a transparent and dynamically reversible gel material;
[0035] Step S22) Organic nanoparticles, organic / inorganic hybrid nanoparticles, cellulose solvent, catalyst and deionized water are mixed in a weight ratio of 48-328:61-352:0.5-4:0.5-2.5:10-30 to obtain a first fire-proof mixed liquid, and stirred at a stirring speed of less than 80r / min at room temperature for 40 minutes to form a uniform suspension; 11-30 weight parts of gelling material are added to the first fire-proof mixed liquid, and stirred at a stirring speed of less than 80r / min at room temperature for 80 minutes to obtain a clear or slightly turbid second fire-proof mixed liquid; 0.5-2.5 weight parts of catalyst and 0.001-0.05 weight parts of defoaming agent are added to the second fire-proof mixed liquid in sequence, and stirred at a stirring speed of less than 80r / min at room temperature for 40 minutes to obtain a fire-proof pre-reaction liquid, which is allowed to stand for use.
[0036] The application of the fireproof pre-reaction liquid is used for flame retardant treatment of transparent cellulose modified soda-lime glass products and forming a fireproof layer with a thickness of 0.02 to 0.3 mm on the surface of the glass products. The specific operation is: spray the fireproof pre-reaction liquid on the surface of the transparent cellulose modified soda-lime glass product, let it stand for 50 minutes, and bake it in a 50°C oven for 4 hours after the surface of the glass product is dry, and then heat it to 80°C and bake it for 3 hours, so that the cellulose on the surface of the glass and the fireproof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure. By means of the above technical scheme, the fireproof layer material and its preparation method and fireproof glass provided by the present invention have at least the following advantages:
[0037] 1. Gradient blending technology and semi-continuous self-assembly technology are used for gradual dispersion, which further optimizes the grading effect of nano-silica particles and greatly reduces the viscosity of the system: the particle size of nano-silica particles prepared by the sol-gel method is 450nm-500nm, which is similar to the particle size of silica particles and their agglomerates obtained by gradient ball milling. Then, a bimodal wide distribution dendritic core-shell structure organic / inorganic hybrid silica particle emulsion is obtained by semi-continuous self-assembly technology. Compared with silica solutions prepared by other technologies, under the premise of the same solid content, the widely distributed nano core-shell structured organic / inorganic hybrid silica particles enable the pre-reaction solution of the fireproof layer material to have the characteristics of shear thinning, have a lower viscosity, and can be infused into a thinner glass cavity faster; at the same time, the silanol groups formed after the hydrolysis of γ-(2,3-epoxypropoxy)allyltrimethoxysilane can react with the silanol groups on the surface of silica, anchored on the surface of silica, and reduce the adsorption of free water in the system by silica particles; its allyl structure can ensure polymerization reaction with acrylamide and butyl acrylate to form a dendritic core-shell structure, prevent the deposition and agglomeration of silica particles, and improve the storage stability of the system.
[0038] 2. By introducing special processes such as low-temperature induced stacking technology and gradient temperature rise reaction in the preparation process of nano core-shell structured organic / inorganic hybrid particles, a synergistic effect is generated between the components of the fireproof layer material, eliminating the bubbles in the composite fireproof glass interlayer, and preparing high-performance microbubble-free, low-temperature, non-insulating composite fireproof glass suitable for outdoor environments with good adhesion, excellent deformation resistance, a transmittance of 85-92%, a fire-resistant integrity time of up to about 400 minutes, and ultraviolet radiation resistance time of more than 3000 hours. It can be used in low temperature environments (-50°C).
[0039] 3. The reason why the fireproof layer material of the present invention has excellent low temperature resistance, deformation resistance and fireproof integrity is that the specially designed gradient blending technology and semi-continuous self-assembly process optimize the grading effect of nano core-shell structure organic / inorganic hybrid particles, reduce the viscosity of the reaction system, and ensure that the solid content of silicon dioxide is further increased (can exceed 55%). Correspondingly, the free water in the fireproof layer material is reduced; compared with the "homogeneous" structure, the "thousand-layer cake" type super-multilayer structure increases the strength of the fireproof layer material in the vertical direction and reduces the rate of deformation; during the fire test, the fire-facing glass breaks rapidly, and the fireproof material with the "thousand-layer cake" type super-multilayer structure will not have the situation of overall uneven foaming, but expands layer by layer under the action of high temperature (about 1000°C) to form a dense protective layer. Even if most of the K2O﹒nSiO2 fireproof material is peeled off due to the shedding of the fire-facing glass, there is still a thin protective layer on the other glass on the back of the fire, which ensures the integrity of the back of the fire glass and prevents the spread of flames.
[0040] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a schematic diagram of the structure of the organic nanoparticles in the present invention;
[0042] Figure 2 Schematic diagram of the structure of organic / inorganic hybrid nanoparticles in the present invention.
[0043] 1-flexible core layer; 2-reinforced transition layer; 3-shell layer; 4-silicon dioxide particles; 5-linear ammonium polyphosphate polymer; 6-linear glycidyl methacrylate polymer DETAILED DESCRIPTION
[0044] The nanocomposite material of the present invention is composed of two nanoparticles. In the multi-layer core-shell structure of each nanoparticle, a reinforcing transition layer is provided between the flexible core layer and the outermost shell layer, and the reinforcing transition layer is a polymer layer containing melamine formaldehyde material with a cross-linked network structure. In the two nanoparticles, the outermost layer of the organic nanoparticle is a graft formed by a phosphorus-containing polymer, and the outermost layer of the organic / inorganic hybrid nanoparticle is a graft formed by an epoxy-containing polymer, wherein the graft of the outermost layer of the organic nanoparticle and the graft of the outermost layer of the organic / inorganic hybrid nanoparticle are both thorn-like objects on the surface of a roxburghii; at least one polymer in the two nanoparticles can form a fireproof layer of an interpenetrating network structure with cellulose. Among them, the nanoparticles with a multilayer core-shell structure are narrowly distributed particles prepared by soap-free emulsion polymerization and particle design principles. For organic nanoparticles, the flexible core layer material is polyacrylamide particles and aggregates thereof, and the materials wrapped on the polyacrylamide particles are poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked structure, a shell layer composed of a reinforcing transition layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) copolymer, and a shell composed of linear ammonium polyphosphate. layer surface grafts; for organic / inorganic hybrid nanoparticles, the flexible core layer material is polyacrylamide particles and their aggregates, and the materials wrapped on the polyacrylamide particles are respectively a reinforcing transition layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked structure, a shell layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and double bonds, and a shell graft composed of linear poly(glycidyl methacrylate) copolymer. The fireproof pre-reaction liquid containing the nano-composite material is composed of the following substances in parts by weight: 2-3 parts of tetraethyl orthosilicate, 0.02-0.04 parts of concentrated ammonia water with a concentration of 25wt%, 47-116 parts of deionized water, 0.1-1 parts of vinyl silane coupling agent, 0.501-1.02 parts of ethanol, 40-300 parts of polyacrylamide solution, 0.4-52 parts of butyl acrylate, 1.2-14 parts of methyl methacrylate, 0.2-40 parts of melamine, 0.2-40 parts of styrene, and 0.02-0.06 parts of divinyl sulfone. parts, 0.1-0.4 parts of 20wt% ammonia water, 0.2-40 parts of 2,4-methyl-3-cyclohexene carboxaldehyde, 0.2-12 parts of methacrylic acid, 0.1-1 parts of 3-butene-1-amine, 5-15 parts of ammonium polyphosphate, 5-15 parts of glycidyl methacrylate, 0.024-0.2 parts of emulsifier, 0.026-2.26 parts of initiator, 1-5 parts of carbonizing agent, 0.1-1 parts of rheological additive, 0.5-4 parts of cellulose solvent, 0.5-2.5 parts of catalyst and 0.001-0.05 parts of defoaming agent.Among them, organic nanoparticles and organic / inorganic hybrid nanoparticles are both single-peak, narrowly distributed particles; the two nanoparticles with nano core-shell structures are both narrowly distributed particles prepared by soap-free emulsion polymerization and particle design principles. For organic nanoparticles, their flexible core layer materials are polyacrylamide particles and their aggregates, their reinforcing transition layer materials are cross-linked poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymers, shell materials are amino-containing poly(butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) copolymers, and shell materials are 1-hydroxy-1-butylene-1-amine copolymers. The surface grafted material is linear ammonium polyphosphate; for organic / inorganic hybrid nanoparticles, the flexible core layer material is polyacrylamide particles and their aggregates, the reinforcing transition layer material is poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked structure, the shell layer material is poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and double bonds, and the shell layer surface grafted material is linear poly(glycidyl methacrylate) copolymer; the pH value of the fireproof material pre-reaction liquid is between 5.5 and 8.5.
[0045] In the present invention, the organic nanoparticles do not contain silica particles, which can provide better toughness for the fireproof layer made of the nanocomposite material of the present invention, while the organic / inorganic hybrid nanoparticles contain silica particles, which can provide better hardness for the fireproof layer made of the nanocomposite material of the present invention, thereby ensuring that the fireproof layer is not easy to break while having a certain impact resistance.
[0046] As a preferred embodiment, the fire-proof pre-reaction liquid is composed of the following raw materials in parts by weight: 2.1-2.7 parts of tetraethyl orthosilicate, 0.025-0.035 parts of concentrated ammonia water with a concentration of 25wt%, 65-110 parts of deionized water, 0.2-0.8 parts of vinyl silane coupling agent, 0.6-0.9 parts of ethanol, 30-120 parts of polyacrylamide solution, 5-35 parts of butyl acrylate, 3-10 parts of methyl methacrylate, 3-20 parts of melamine, 3-20 parts of styrene, 0.05-0.05 parts of divinyl sulfone, The invention discloses a 20wt% aqueous ammonia solution comprising 0.15 to 0.35 parts, 2,4-methyl-3-cyclohexene carboxaldehyde 3 to 20 parts, methacrylic acid 3 to 10 parts, 3-butene-1-amine 0.2 to 0.8 parts, ammonium polyphosphate 7.5 to 12 parts, glycidyl methacrylate 7.5 to 12 parts, an emulsifier 0.04 to 0.16 parts, an initiator 0.5 to 1.5 parts, a carbonizing agent 1.5 to 3.5 parts, a rheological agent 0.2 to 0.8 parts, a cellulose solvent 1 to 3.5 parts, a catalyst 0.8 to 2 parts and a defoaming agent 0.005 to 0.04 parts.
[0047] As a preferred embodiment, the solid content of the polyacrylamide emulsion is 35wt% to 45wt%, the degree of polymerization of the polyacrylamide particles is 15000 to 25000, the particle size is 50nm to 80nm, the particle size distribution is a single peak narrow distribution, the thickness of the reinforcing transition layer, the shell thickness and the shell surface graft thickness of the organic nanoparticles and organic / inorganic hybrid nanoparticles are 35nm to 45nm, 25nm to 35nm, and 40nm to 120nm, respectively.
[0048] The invention uses a nano composite material as the main raw material of a fireproof material. The particle size of the polyacrylamide particles in the polyacrylamide emulsion is 40nm-200nm, the solid content is 15wt%-55wt%, the flexible core layer particle size of the two nano particles is both 40nm-200nm, and the particle size distribution is a single peak narrow distribution; for the organic nano particles: the reinforcing transition layer material is a poly (butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked network structure and containing a melamine formaldehyde material, and the thickness of the reinforcing transition layer is 35nm-45nm; the shell layer material is a poly (butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) copolymer containing an amino group, and the thickness of the shell layer is 25nm-35nm; and the shell layer surface graft is a linear ammonium polyphosphate, and the thickness of the shell layer surface graft is 40nm-120nm. For organic / inorganic hybrid nanoparticles: the reinforcing transition layer material is a first shell layer of a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing a melamine formaldehyde material having a cross-linked network structure, and the reinforcing transition layer thickness is 20nm to 30nm; the shell material is a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and containing double bonds, and the shell thickness is 25nm to 35nm; and the shell surface graft is a linear poly(glycidyl methacrylate polymer, and the shell surface graft thickness is 40nm to 120nm. Both of the nanoparticles are narrow distribution particles. The present invention has the characteristics of multiple cross-linking system, low viscosity of pre-reaction liquid, good impact resistance of coating and water washing resistance. At the same time, the low-temperature use temperature can reach -35°C±1°C, the coating is resistant to ultraviolet radiation for more than 2000 hours, and the flame retardant grade meets the B1 low flammability material standard specified in DIN4102 (German standard) and UL94-V0 high flame retardant material standard (American Insurance Association standard).
[0049] The fireproof pre-reaction liquid of the present invention exists in the form of a dispersion liquid, and the mass concentration of the dispersion liquid is 40%-60%.
[0050] As a preferred embodiment, the emulsifier is at least one of reactive emulsifiers (such as nonylphenol allyl polyoxyethylene ether ammonium sulfate, allyloxydecyl polyoxyethylene ether ammonium sulfate, etc.); the initiator is at least one of thermal initiators (such as dibenzoyl peroxide, azobisisobutyronitrile, etc.) and redox initiators (such as ammonium persulfate and sodium bisulfite, etc.); the alkenyl silane coupling agent is at least one of vinyl triperoxide tert-butyl silane, vinyl triethoxysilane, butadienyl triethoxysilane, vinyl trimethoxysilane, isobutylenyl triethoxysilane, and vinyl tri(β-methoxyethoxy) silane; the carbon-forming agent is a material compounded with at least one of sucrose, fructose, glucose and maltose and pentaerythritol; the rheological additive is hydroxymethyl cellulose, methyl cellulose , ethyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose; the cellulose solvent is at least one solution of dipropylene glycol methyl ether and N-methylmorpholine oxide; the pigment is at least one material selected from organic pigments and inorganic pigments; the pigment auxiliary agent is at least one material selected from N-methylpyrrolidone, N-ethylpyrrolidone, Nd butylpyrrolidone, and N-octylpyrrolidone; the catalyst is a material compounded with at least one of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite and a dilute hydrochloric acid solution (≤20wt%); the defoamer is at least one selected from polysiloxane defoamers (such as BYK024, BYK088) and polyether defoamers (such as GP-type glycerol polyether, GPE-type polyoxyethylene (polyoxypropylene) ether, and PPG-type polypropylene glycol).
[0051] The functions of the raw materials used in the fire-proof pre-reaction liquid of the present invention are as follows:
[0052] The two types of nanoparticles are mixed with a solvent to form a fire-retardant pre-reaction liquid of polyacrylamide-based latex particles with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking. After the fire-retardant pre-reaction liquid comes into contact with transparent cellulose-modified soda-lime glass, it can penetrate into the multiple cross-linking network to form physical cross-links, thereby further entangled with the cellulose on the glass surface and increasing the cross-linking degree of the coating; at the same time, this "sea buckthorn"-shaped structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.
[0053] The two nanoparticles used in the embodiments of the present invention are of a core-shell structure, which means that two or more monomers are polymerized in stages or multiple stages under certain conditions, so that different components are enriched on the inside or outside of the particles, i.e., core-shell particles, thereby giving the core and the shell different functions and obtaining particles with excellent performance; wherein the flexible core layer material is polyacrylamide particles and their agglomerates. For organic nanoparticles: the reinforcing transition layer material is a first shell layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked network structure containing melamine formaldehyde material, the functional shell material is a second shell layer of poly(butyl acrylate-methyl methacrylate-methacrylate-3-butene-1-amine) copolymer containing amino groups, and the shell surface graft is linear ammonium polyphosphate; for organic / inorganic hybrid nanoparticles: the reinforcing transition layer material is a first shell layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked network structure containing melamine formaldehyde material, the functional shell material is a second shell layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and containing double bonds, and the shell surface graft is a linear poly(glycidyl methacrylate) copolymer. This specially designed multi-layer core-shell structure and preparation process optimizes the particles themselves and the effective cross-linking between particles, reduces the swelling degree of the multi-layer core-shell latex particles and the film layer, and further improves the density of the particles in the film-forming process. On the basis of improving the strength of the film polymer, the water content in the film is reduced, and accordingly, the destruction of the internal structure of the film by ice crystals at low temperatures is avoided; the multiple cross-linking system also increases the ultraviolet radiation resistance of the film; at the same time, polymers with butylamine (3-butene-1-amine) and double-bonded silica particles are polymerized in the functional shell layer respectively to achieve the uniform distribution of "sea buckthorn"-shaped linear ammonium polyphosphate and polymethacrylic acid molecular chains on the outer surface of the latex particles. With the help of the high hardness of silica inorganic particles, the advantage of "soft core and hard shell" of latex particles is achieved. The soft core can ensure that the coating has excellent impact resistance, and the organic\inorganic composite hard shell with a cross-linked structure gives the coating scratch resistance, and can also improve the coating hardness and ultraviolet radiation resistance.
[0054] The above two nanoparticles are narrow distribution nanoparticles, and their particle sizes are 140nm-400nm. The study found that: relying on the principle of "particle design", the fire-retardant pre-reaction liquid composed of two nanoparticles with multi-layer core-shell structure and low viscosity has shear-thinning characteristics because the entanglement between the outermost branched polymers is only physical entanglement. Through the optimization of other additives, the addition of other additives does not affect the shear-thinning characteristics of the system. Therefore, the prepared fire-retardant pre-reaction liquid also has shear-thinning characteristics.
[0055] Since both nanoparticles are narrowly distributed nanoparticles, they have multiple cross-linking systems, low viscosity of the pre-reaction liquid, good impact resistance of the coating, and water washing resistance. At the same time, the low-temperature use temperature can reach -25℃±1℃, the coating is resistant to ultraviolet radiation for more than 2000 hours, and the flame retardant grade meets the B1 low flammability material standard (German standard) specified in DIN4102 and the UL94-V0 high flame retardant material standard (American Insurance Association standard). The above two nanoparticles, respectively, introduce butylamine (3-butene-1-amine) polymers in the functional layer and double bonds (alkenyl silane coupling agents) on the hydrophilic silica surface, providing reaction sites for the two outermost linear polymers (ammonium polyphosphate and poly(glycidyl methacrylate)) to be grafted onto the core-shell polymer surface: the amino groups in the functional shell polymer of the organic nanoparticles can graft ammonium polyphosphate onto the shell surface through ion exchange reaction in ethanol solution to obtain linear grafted ammonium polyphosphate; at the same time, the organic / inorganic hybrid nanoparticles The olefin groups in the subfunctional shell layer can undergo polymerization reaction with glycidyl methacrylate to form linear polyglycidyl methacrylate polymers, which provide precursors for the subsequent ring-opening and curing of the epoxy groups with ionic reaction activity, thereby forming a material with a multiple network structure. The use of cellulose-based substances as rheological additives in the fire-retardant pre-reaction liquid can improve the leveling properties of the system during painting, and can also penetrate into multiple cross-linked networks to form physical cross-links, thereby further entangled with the cellulose on the surface of the transparent cellulose-modified soda-lime glass for construction, thereby increasing the degree of cross-linking of the coating.
[0056] It should be emphasized that in the fireproof pre-reaction liquid of the present invention, the nano core-shell structure organic-inorganic hybrid particles themselves have the properties of resistance to low temperature, resistance to ultraviolet radiation, resistance to impact, and resistance to water washing.
[0057] The reason why the nanocomposite material itself is resistant to low temperature, UV radiation, impact and water washing is:
[0058] 1. The specially designed multi-layer core-shell structure and preparation process optimize the effective cross-linking between particles, reduce the swelling degree of the multi-layer core-shell latex particles and the film layer caused by the solvent in the system and the moisture in the use environment, further improve the density of the particles in the film forming process, and reduce the moisture content in the film layer on the basis of improving the strength of the film polymer. Accordingly, it avoids the destruction of the internal structure of the film layer by ice crystals at low temperatures;
[0059] 2. The multiple cross-linking system also increases the film's resistance to ultraviolet radiation;
[0060] 3. By introducing butylamine (3-butene-1-amine) polymers into the functional layer and double bonds (alkenyl silane coupling agents) onto the surface of hydrophilic silica particles, the uniform distribution of "roebergia"-shaped linear ammonium polyphosphate and polymethacrylic acid molecular chains on the outer surface of latex particles is achieved. With the high hardness of inorganic silica particles, the advantages of "soft core and hard shell" of latex particles are achieved. The soft core can ensure that the coating has excellent impact resistance, and the cross-linked organic\inorganic composite hard shell gives the coating scratch resistance and improves the coating's resistance to ultraviolet radiation.
[0061] 4. The "sea buckthorn"-like structure increases the entanglement between the film layer and the cellulose on the glass surface, while the multiple network cross-linked structures firmly fix these entanglements together, improving the adhesion of the coating. At the same time, this "rambutan"-like structure can give the coating a "lotus leaf effect", further improving the coating's resistance to water washing.
[0062] The fireproof pre-reaction liquid containing two nanoparticles having a "roxburghii"-shaped multi-layer core-shell structure is prepared by the following steps:
[0063] Mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm;
[0064] Put the silica seed solution, alkenyl silane coupling agent and ethanol into a high-pressure homogenizer according to 10-25: 0.1-1: 0.001-0.02 for circulation dispersion for 10 minutes, put it into a three-necked flask, and then put the three-necked flask into a water bath pot at 70°C-90°C, stir and disperse at a stirring speed of 100-150r / min for 30 minutes, and then cool to 20°C to obtain a silica dispersion with double bonds on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11);
[0065] The first mixed solution is prepared by mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt% ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and reactive emulsifier in weight proportions of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08; 0.5-80 weight parts of the first mixed solution, 6-12 weight parts of deionized water and 0.005-1 weight parts of initiator at a constant speed under a temperature of 60-65°C by means of starvation polymerization; The agent is added dropwise into 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt%. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion with a cross-linked core-shell structure; butyl acrylate, methyl methacrylate, methacrylic acid, 3-butene-1-amine and a reactive emulsifier are mixed in a ratio of 0.1 to 6:0.1 to 6:0.1 to 6:0.1 to 1: The invention relates to a method for preparing a second mixed solution by mixing 0.01 to 0.02 parts by weight of the first polymer template latex with 0.1 to 19 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, and 0.003 to 0.03 parts by weight of an initiator at a temperature of 60 to 65° C. at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) material containing an amino group is coated on the surface of the polyacrylamide latex particles to obtain a second polymer template latex having a multilayer core-shell structure. Polymer template latex; preparing an emulsion containing organic nanoparticles: by means of ion exchange reaction, 7 to 26 parts by weight of the third mixed solution are added dropwise to 41 to 302 parts by weight of the second polymer template latex at a constant speed under a temperature condition of 30 to 40°C, stirred at a stirring speed lower than 80r / min, and refluxed and condensed under this temperature condition for 4 hours to form a polymer with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles to obtain an emulsion containing organic nanoparticles; furthermore, organic nanoparticles having a "sea buckthorn"-shaped multi-layer core-shell structure and capable of multiple crosslinking can be obtained.
[0066] The fourth mixed solution is prepared by mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in the weight proportion of 0.1-6:0.1-6:0.1-6:0.01-0.02. By means of starvation polymerization, 0.1-18 weight parts of the fourth mixed solution, 15-40 weight parts of deionized water, 10-26 weight parts of a silicon dioxide dispersion with double bonds on the surface and 0.003-0.03 weight parts of an initiator are added dropwise to 26-242 weight parts of a first polymer template latex at a constant speed under a temperature condition of 60-65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate) embedded with silicon dioxide particles with a particle size of 20 nm to 30 nm and double bonds is coated on the surface of the polyacrylamide latex particles. A third polymer template emulsion with a bayberry-like multilayer core-shell structure is obtained by preparing a material of methyl methacrylate-methyl methacrylate) and a third polymer template emulsion with a bayberry-like multilayer core-shell structure; a fifth mixed solution is prepared by mixing glycidyl methacrylate, an initiator and deionized water in a ratio of 5-15:0.01-0.2:5-10 by weight; 10-25 parts by weight of the fifth mixed solution are added dropwise to 51-327 parts by weight of the third polymer template emulsion at a constant speed under a temperature condition of 60-65°C, and stirred at a stirring speed lower than 80r / min, and refluxed and condensed under this temperature condition for 3h to form a second polymer with linear poly(glycidyl methacrylate) as a branch on the surface of the latex particles, thereby obtaining organic / inorganic hybrid nanoparticles with a "sea buckthorn"-like multilayer core-shell structure and multiple cross-linking.
[0067] The carbonizing agent, the rheological additive and the deionized water are mixed in a weight ratio of 1-5:0.1-1:10-25, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and aged for 12 hours to obtain a transparent and dynamically reversible gel material;
[0068] Organic nanoparticles, organic / inorganic hybrid nanoparticles, cellulose solvent, catalyst and deionized water are mixed in a weight ratio of 48-328:61-352:0.5-4:0.5-2.5:10-30 to obtain a first fireproof mixed liquid, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; 11-30 parts by weight of gelling material are added to the first fireproof mixed liquid, and stirred at a stirring speed of less than 80 r / min for 80 minutes at room temperature to obtain a clear or slightly turbid second fireproof mixed liquid; 0.5-2.5 parts by weight of catalyst and 0.001-0.05 parts by weight of defoaming agent are added to the second fireproof mixed liquid in sequence, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fireproof pre-reaction liquid, which is left to stand for use;
[0069] In accordance with the standard requirements of XF 159-2011 "Water-based flame retardants", the fire-retardant pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, left to stand for 50 minutes, and then placed in a 50°C oven for 4 hours after the surface of the glass product is dry, and then heated to 80°C and baked for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.
[0070] Furthermore, in the above steps, the particle size of the polyacrylamide particles in the polyacrylamide emulsion is 40nm-200nm, the solid content is 15wt%-55wt%, the particle size of the flexible core layer of the two nanoparticles is 40nm-200nm, and the particle size distribution is also a single peak narrow distribution; the reinforcing transition layer material of the two nanoparticles is the first shell layer of poly (butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing melamine formaldehyde material with a cross-linked network structure, the functional shell material is (butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) copolymer containing amino groups, and the shell thickness is 25nm-35nm; and the shell surface graft material is linear ammonium polyphosphate or linear polymethacrylate glycidyl ester polymer, and the shell surface graft thickness is 40nm-120nm. The two nanoparticles are narrow distribution particles.
[0071] Furthermore, in the above step S16), the stirring time is 20 to 60 minutes, preferably 40 minutes.
[0072] When preparing the fireproof pre-reaction liquid in the embodiment of the present invention, firstly, tetraethyl orthosilicate, ammonia water with a concentration of 20%, and deionized water are mixed, and the mixture is allowed to stand for aging to obtain a silicon dioxide seed solution; the silicon dioxide seed solution, alkenyl silane coupling agent, and ethanol are dispersed homogenously under high pressure, and the mixture is stirred and reacted at a stirring speed of less than 150 r / min to obtain a silicon dioxide dispersion liquid with alkenyl groups on the surface; butyl acrylate, melamine, styrene, divinyl sulfone, ammonia water with a concentration of 20wt%, 2,4-methyl-3-cyclohexene formaldehyde, and a reactive emulsifier are mixed to obtain a first mixed solution; the first mixed solution, deionized water, and an initiator are added dropwise to a polyacrylamide emulsion by means of a starvation polymerization method to obtain a first polymer template emulsion having a cross-linked core-shell structure; Butyl acrylate, methyl methacrylate, methacrylic acid, 3-butene-1-amine and a reactive emulsifier are mixed to prepare a second mixed solution; the second mixed solution, deionized water, a silicon dioxide dispersion with amino groups on the surface and an initiator are dripped into a first polymer template emulsion by means of a starvation polymerization method to obtain a second polymer template emulsion with a multi-layer core-shell structure; ammonium polyphosphate, ethanol and deionized water are mixed to prepare a third mixed solution; the third mixed solution is dripped into the second polymer template emulsion by means of an ion exchange reaction, and a reflux condensation reaction is performed to obtain a polymer emulsion having a "roxil" shape, a linear ammonium polyphosphate as the outermost branch chain, and a multi-crosslinkable organic multi-layer core-shell structure; butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier are mixed to prepare a second mixed solution; the second mixed solution, deionized water, ethanol and deionized water are dripped into a third mixed solution; the third mixed solution is dripped into the second polymer template emulsion by means of an ion exchange reaction, and a reflux condensation reaction is performed to obtain a polymer emulsion having a "roxil" shape, a linear ammonium polyphosphate as the outermost branch chain, and a multi-crosslinkable organic multi-layer core-shell structure; The fourth mixed solution, ionized water, silica dispersion with double bonds on the surface, and initiator are added dropwise to the first polymer template emulsion to obtain a third polymer template emulsion with a multi-layer core-shell structure; methacrylate glycidyl ester, initiator, and deionized water are mixed to obtain a third mixed solution; the fifth mixed solution is added dropwise to the third polymer template emulsion at a constant speed, and refluxed for condensation to obtain a polymer emulsion having a "roxburghii" shape, a linear polymethacrylate glycidyl ester polymer as the outermost branch chain, and a multi-crosslinkable organic / inorganic multi-layer core-shell structure; a carbonizing agent, a rheological additive, and deionized water are mixed, stirred at a stirring speed of less than 100 r / min, and allowed to stand for aging to obtain a gel. Materials: organic / inorganic hybrid nanoparticles with a "sea buckthorn"-shaped multilayer core-shell structure and multiple cross-linking, a cellulose solvent, a catalyst, and deionized water are mixed, and stirred at a stirring speed of less than 80 r / min, and then a gelling material is added thereto, and stirred at a stirring speed of less than 80 r / min to obtain a pre-reaction liquid; the catalyst and the defoaming agent are added to the pre-reaction liquid in sequence, and stirred at a stirring speed of less than 80 r / min to obtain a fire-proof pre-reaction liquid on the surface of a transparent cellulose-modified soda-lime glass product, and the fire-proof pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, and the surface of the glass product is baked after it is dried, so that the cellulose on the glass surface and the fire-proof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure, thereby improving the flame retardant properties of the product.
[0073] The fireproof material formed after the fireproof pre-reaction liquid provided by the embodiment of the present invention reacts is an intumescent flame retardant system. When encountering a fire, the ammonium polyphosphate on the surface of the glass cellulose is thermally decomposed to generate phosphoric acid and pyrophosphoric acid with strong dehydration effect, so that the carbon forming agent is esterified, and then dehydrated and carbonized. The water vapor formed by the reaction and the ammonia decomposed in the melamine formaldehyde resin can also expand the carbon layer, and finally form a multi-porous carbon layer, thereby isolating air and heat conduction, protecting glass products, and achieving the purpose of flame retardancy. At the same time, the fireproof material formed after the fireproof pre-reaction liquid provided by the embodiment of the present invention reacts has the following advantages: good thermal stability, and the multiple cross-linking system ensures that the coating can withstand high temperature reprocessing above 150°C after low-temperature baking; when a fire suddenly occurs, a large amount of volatile substances can be released, blocking oxygen, and expanding and foaming at the same time; this "thorn pear"-shaped multi-layer core-shell structure and multi-crosslinkable fireproof structure can be evenly distributed on the surface of the wood fiber during the film forming process, and can form a layer of expanded carbon that completely covers the surface of the material in the fire to prevent it from dripping and spreading the fire.
[0074] As a preferred embodiment, the thickness of the fireproof layer is 0.02-0.3 mm.
[0075] The present invention can control the thickness of the fireproof layer formed by the fireproof pre-reaction liquid on the glass surface to 0.02-0.3mm, and manufacture a thinner fireproof layer under the premise of ensuring fireproof performance, reduce the production cost of the window, and expand the application scope of the fireproof material. The fireproof material formed by the fireproof pre-reaction liquid of the embodiment of the present invention will expand to form a porous heat-insulating layer after encountering fire, and the thickness of the expansion layer is about 15 to 20 times the thickness of the original fireproof layer, and gradually forms a heat-insulating layer of about 1mm to 4mm; if the thickness of the fireproof material is less than 0.02mm, the fireproof layer is too thin, and the formed heat-insulating layer cannot isolate the heat transfer within a certain period of time, resulting in the overall fireproof time being lower than the design value; if the thickness of the fireproof material is greater than 0.3mm, the fireproof layer is too thick, which will cause the excess fireproof pre-reaction liquid on the glass surface to be unable to continue to form an effective network entanglement with cellulose, and also block the volatilization of the solution inside the coating, so that the early baking time is greatly increased, the cost is too high, and the fireproof performance is reduced.
[0076] The present invention is further described below with reference to specific embodiments, but is not intended to limit the present invention.
[0077] The reagents used in the embodiments of the present invention are all commercially available products.
[0078] Example 1
[0079] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0080] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0081] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of 20wt% ammonia water, 8kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0082] Since the particle size of the latex particles in the polyacrylamide emulsion is narrowly distributed, the particle sizes of the two nanoparticles are also unimodal, and similarly, the particle sizes of the flexible core layer particles and the two nanoparticles in the following examples are also narrowly distributed;
[0083] (2) Prepare a fire-proof pre-reaction liquid by the following steps:
[0084] 2.3 kg of tetraethyl orthosilicate, 0.03 kg of concentrated ammonia water with a concentration of 25 wt%, and 15 kg of deionized water were mixed and allowed to stand for 36 hours to generate a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, and the particle size of the silicon dioxide particles was 20 nm to 30 nm;
[0085] 12.5 kg of silica seed solution, 0.3 kg of alkenyl silane coupling agent and 0.01 kg of ethanol were placed in a high-pressure homogenizer for circulation dispersion for 10 minutes, and then placed in a three-necked flask, and then the three-necked flask was placed in a water bath at 70°C to 90°C, stirred and dispersed at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooled to 20°C to obtain a silica dispersion with double bonds on the surface;
[0086] 5 kg of butyl acrylate, 3 kg of melamine, 3 kg of styrene, 0.02 kg of divinyl sulfone, 0.1 kg of 20 wt% ammonia water, 4 kg of 2,4-methyl-3-cyclohexene carboxaldehyde, and 0.04 kg of emulsifier are mixed to prepare a first mixed solution; by means of starvation polymerization, 15.16 kg of the first mixed solution, 7.5 kg of deionized water, and 0.05 kg of initiator are added dropwise to 40 kg of polyacrylamide emulsion with a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion with a cross-linked core-shell structure;
[0087] 2kg of butyl acrylate, 2kg of methyl methacrylate, 2kg of methacrylic acid, 0.3kg of 3-butene-1-amine, and 0.015kg of an emulsifier are used to prepare a second mixed solution; 6.315kg of the second mixed solution, 20kg of deionized water, and 0.02kg of an initiator are added dropwise to 62.71kg of the first polymer template latex at a constant speed under a temperature condition of 60-65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) material containing an amino group is coated on the surface of the polyacrylamide latex particles to obtain a second polymer template latex having a multilayer core-shell structure;
[0088] A third mixed solution is prepared by using 10 kg of ammonium polyphosphate, 0.7 kg of ethanol and 5 kg of deionized water; by means of ion exchange reaction, 15.7 kg of the third mixed solution is added dropwise to 89.045 kg of the second polymer template latex at a constant speed under a temperature condition of 30 to 40° C., stirred at a stirring speed lower than 80 r / min, and refluxed and condensed for 4 hours under this temperature condition to form a first polymer latex with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles; and organic nanoparticles having a "roxburghii"-shaped multi-layer core-shell structure and capable of multiple crosslinking are obtained;
[0089] 2kg of butyl acrylate, 2kg of methyl methacrylate, 2kg of methacrylic acid, and 0.015kg of an emulsifier are used to prepare a fourth mixed solution; 6.015kg of the fourth mixed solution, 20kg of deionized water, 12.81kg of a silica dispersion with double bonds on the surface, and 0.02kg of an initiator are added dropwise to 62.71kg of the first polymer template emulsion at a constant speed under a temperature condition of 60-65°C by means of a starvation polymerization method; after the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silica particles with double bonds having a particle size of 20nm-30nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a third polymer template emulsion having a bayberry-like multilayer core-shell structure;
[0090] A fifth mixed solution was prepared by adding 10 kg of glycidyl methacrylate, 0.15 kg of initiator and 7.5 kg of deionized water; by means of starvation polymerization, 17.65 kg of the fifth mixed solution was added dropwise to 101.555 parts by weight of the third polymer template latex at a constant speed under a temperature condition of 60-65°C, and stirred at a stirring speed of less than 80 r / min, and refluxed and condensed under this temperature condition for 4 hours to form a first polymer latex with a linear poly(glycidyl methacrylate) polymer as the outermost branch chain on the surface of the latex particles; and organic nanoparticles with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking were obtained.
[0091] 3 kg of carbonizing agent, 0.5 kg of rheological additive and 20 kg of deionized water were mixed, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and then aged for 12 hours to obtain a transparent, dynamically reversible gel material;
[0092] 104.745 kg of organic nanoparticles, 119.205 kg of organic / inorganic hybrid nanoparticles, and 3 kg of cellulose solvent were stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; 23.5 kg of a transparent, dynamically reversible gelling material was added thereto, and stirred at a stirring speed of less than 100 r / min for 60 minutes at room temperature to obtain a clear or slightly turbid pre-reaction liquid; 1.5 kg of a catalyst and 0.02 kg of a defoaming agent were added to the pre-reaction liquid in sequence, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fire-proof pre-reaction liquid for the surface of wooden products for railway vehicles, which was left to stand for use;
[0093] In accordance with the standard requirements of XF 159-2011 "Water-based flame retardants", the fire-retardant pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, left to stand for 50 minutes, and after the surface of the glass product is dry, it is placed in a 50°C oven and baked for 4 hours, and then heated to 80°C and baked for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure, thereby improving the flame retardant properties of the product.
[0094] Example 2
[0095] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0096] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0097] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 5.5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 7.5kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0098] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0099] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0100] Example 3
[0101] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0102] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0103] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 7kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent
[0104] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0105] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0106] Example 4
[0107] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0108] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0109] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 4.5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of 20wt% ammonia water, 6.5kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0110] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0111] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0112] Example 5
[0113] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0114] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0115] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 4kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of 20wt% ammonia water, 6kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0116] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0117] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0118] Example 6
[0119] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0120] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0121] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6.5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8.5kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0122] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0123] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0124] Example 7
[0125] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0126] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0127] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 2.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0128] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0129] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0130] Example 8
[0131] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0132] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0133] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of 20wt% ammonia water, 8kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0134] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0135] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0136] Example 9
[0137] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0138] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0139] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.8kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0140] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0141] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0142] Example 10
[0143] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0144] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0145] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.05kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0146] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0147] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0148] Embodiment 11
[0149] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0150] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0151] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 102.5kg of deionized water, 0.3kg of vinyl silane coupling agent, 0.71kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.03kg of divinyl sulfone, 0.2kg of 20wt% ammonia water, 8kg of 2,4-methyl-3-cyclohexenecarboxaldehyde, 4kg of methacrylic acid, 0.3kg of 3-butene-1-amine, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0152] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0153] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0154] Comparative Example 1
[0155] This comparative example provides a fire-proof pre-reaction liquid, the raw materials of which are 55kg deionized water, 3kg melamine, 4kg 2,4-methyl-3-cyclohexene carboxaldehyde, 10kg ammonium polyphosphate, 10kg glycidyl methacrylate, 0.05kg initiator, 3kg carbonizing agent, 0.5kg rheological additive, 3kg cellulose solvent, 1.5kg catalyst, and 0.02kg defoamer. The preparation method of the fire-proof pre-reaction liquid in this comparative example is the same as the preparation method of the fire-proof pre-reaction liquid in Example 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0156] Comparative Example 2
[0157] This comparative example provides a fire-proof pre-reaction liquid, whose raw materials are 55kg of deionized water, 3kg of melamine, 4kg of 2,4-methyl-3-cyclohexene formaldehyde, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.05kg of initiator, 1.5kg of catalyst, and 0.02kg of defoamer.
[0158] The preparation method of the fire-proof pre-reaction liquid in this comparative example is the same as the preparation method of the fire-proof pre-reaction liquid in Example 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0159] Comparative Example 3
[0160] This comparative example is a transparent cellulose-modified soda-lime glass product that has not been flame-retardant treated.
[0161] According to the standard requirements of XF 159-2011 "Water-based Flame Retardant", the flame retardant performance test was conducted on the glass samples coated with the fire-retardant pre-reaction liquid provided in Examples 1 to 12 and Comparative Examples 1 to 3. Four parallel samples were taken in the experiment, and the average value of the data was taken as the experimental result; the viscosity of the fire-retardant pre-reaction liquid was measured according to the GB / T1723 coating viscosity determination method; and the apparent quality of each wooden product was obtained by naked eye observation. The performance parameters of the fire-retardant pre-reaction liquid prepared in the examples of the present invention and the comparative examples are shown in Table 1.
[0162] Table 1 Performance parameters of fire retardant pre-reaction liquid
[0163]
[0164] As can be seen from Table 1, the fireproof pre-reaction liquid in the present invention has a long fire-resistant time and water-resistant after solidification, while the fireproof layer formed by the fireproof pre-reaction liquid prepared in the comparative example does not have the characteristics of water-resistant; the fireproof time formed by the fireproof pre-reaction liquid in the present invention after solidification is 1.5-7 times that of the comparative example, and the hardness and ultraviolet radiation resistance time are also significantly higher than the comparative example. The above description uses only 2,4-methyl-3-cyclohexene melamine formaldehyde resin and ammonium polyphosphate as fireproof materials, which are easily washed away during water flushing, seriously affecting the safety of glass windows. The present invention improves the formula of the fireproof pre-reaction liquid, and uses polyacrylamide-based latex particles with a "roxburghii"-shaped multi-layer core-shell structure and a multi-crosslinkable core-shell structure and an auxiliary agent to mix, so that the components of the fireproof pre-reaction liquid produce a synergistic effect, improve the flame retardant properties of the material, especially after water flushing, the flame retardant properties of the glass product are still unaffected, and at the same time, the low temperature resistance of the fireproof layer formed after the fireproof pre-reaction liquid is solidified is also improved, and it can be used in low temperature (-25℃±1℃) and outdoor environment. The fireproof pre-reaction liquid prepared in the embodiment of the present invention has the advantages of low viscosity, high hardness, good adhesion, long flame retardant time, resistance to low temperature and resistance to ultraviolet radiation, and can form a transparent coating when coated on the surface of an object.
[0165] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0166] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A nanocomposite material, characterized in that: The invention comprises organic nanoparticles and organic / inorganic hybrid nanoparticles, wherein both the organic nanoparticles and the organic / inorganic hybrid nanoparticles comprise a flexible core layer, a shell layer and a reinforcing transition layer, wherein the reinforcing transition layer is arranged between the flexible core layer and the shell layer; the surface of the shell layer of the organic nanoparticles is grafted with linear ammonium polyphosphate, and the surface of the shell layer of the organic / inorganic hybrid nanoparticles is grafted with linear poly(glycidyl methacrylate); the flexible core layer is polyacrylamide latex particles, the reinforcing transition layer is a polymer layer containing melamine formaldehyde material with a cross-linked network structure, the shell layer of the organic nanoparticles is a polymer layer containing a phosphorus-containing polymer, and the shell layer of the organic / inorganic hybrid nanoparticles is a polymer layer containing an epoxy polymer; the polymer in the shell layer of the organic nanoparticles and the polymer in the shell layer of the organic / inorganic hybrid nanoparticles both contain at least one polymer that can form an interpenetrating network structure with cellulose; The material composed of organic nanoparticles is made of the following components: 7 to 26 parts by weight of a third mixed solution and 41 to 302 parts by weight of a second polymer template emulsion; the third mixed solution is made of 5 to 15 parts by weight of ammonium polyphosphate, 0.1 to 1 parts by weight of ethanol and 2 to 10 parts by weight of deionized water; the second polymer template emulsion is made of 0.1 to 19 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 0.003 to 0.03 parts by weight of an initiator, and 26 to 243 parts by weight of a first polymer template emulsion; the second mixed solution is made of 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid, 0.1 to 1 parts by weight of 3-butene-1-amine and 0.01 to 0. The first polymer template emulsion is made of 0.4-80 weight parts of the first mixed solution, 6-12 weight parts of deionized water, 0.005-1 weight part of initiator and 20-150 weight parts of polyacrylamide emulsion with a particle size of 40nm-200nm and a solid content of 15wt%-55wt%; the first mixed solution is made of 0.1-20 weight parts of butyl acrylate, 0.1-20 weight parts of melamine, 0.1-20 weight parts of styrene, 0.01-0.03 weight parts of divinyl sulfone, 0.05-0.2 weight parts of 20wt% ammonia water, 0.1-20 weight parts of 2,4-methyl-3-cyclohexene carboxaldehyde and 0.002-0.08 weight parts of reactive emulsifier; The material composed of organic / inorganic hybrid nanoparticles is made of the following components: 10 to 25 parts by weight of a fifth mixed solution and 51 to 327 parts by weight of a fourth polymer template emulsion; the fifth mixed solution is made by mixing 5 to 15 parts by weight of glycidyl methacrylate, 0.01 to 0.2 parts by weight of an initiator and 5 to 10 parts by weight of deionized water; the fourth polymer template emulsion is made by mixing 0.1 to 18 parts by weight of the fourth mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a surface active agent. The invention discloses a hydrophilic silica dispersion with double bonds, 0.003-0.03 parts by weight of an initiator, and 26-243 parts by weight of a first polymer template emulsion; a fourth mixed solution is prepared by mixing 0.1-6 parts by weight of butyl acrylate, 0.1-6 parts by weight of methyl methacrylate, 0.1-6 parts by weight of methacrylic acid, and 0.01-0.02 parts by weight of a reactive emulsifier; and a first polymer template emulsion is prepared by mixing 0.4-80 parts by weight of the first mixed solution, 6-12 parts by weight of a deionized water, and 0.1-6 parts by weight of methyl methacrylate. The first mixed solution is prepared by mixing 0.1-20 parts by weight of butyl acrylate, 0.1-20 parts by weight of melamine, 0.1-20 parts by weight of styrene, 0.01-0.03 parts by weight of divinyl sulfone, 0.05-0.2 parts by weight of 20wt% ammonia water, 0.1-20 parts by weight of 2 ,4-methyl-3-cyclohexene carboxaldehyde and 0.002-0.08 weight parts of reactive emulsifier are mixed; the hydrophilic silica dispersion with double bonds on the surface is made of 10-25 weight parts of silica seed solution, 0.1-1 weight parts of alkenyl silane coupling agent and 0.001-0.02 weight parts of ethanol; the silica seed solution is made of 2-3 weight parts of tetraethyl orthosilicate, 0.02-0.04 weight parts of concentrated ammonia water with a concentration of 25wt% and 8-22 weight parts of deionized water.
2. The nanocomposite material according to claim 1, characterized in that The polymerization degree of the polyacrylamide particles in the polyacrylamide emulsion is 10000-100000, the particle size is 40nm-200nm, and the particle size distribution is a single peak narrow distribution.
3. The nanocomposite material according to claim 1, characterized in that The alkenyl silane coupling agent is one or more of vinyl tert-butyl triperoxide silane, vinyl triethoxy silane, butadienyl triethoxy silane, vinyl trimethoxy silane, isobutylenyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane.
4. The nanocomposite material according to claim 1, characterized in that The initiator is one or both of a thermal initiator and a redox initiator.
5. The nanocomposite material according to claim 1, characterized in that The emulsifier is a reactive emulsifier.
6. The method for preparing the nanocomposite material according to claim 1, characterized in that: The steps include: S11) preparing a silicon dioxide seed solution: mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm; S12) preparing a silica dispersion with double bonds on the surface: placing a silica seed solution, an alkenyl silane coupling agent and ethanol in a weight ratio of 10-25:0.1-1:0.001-0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes, placing the mixture in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C-90°C, stirring and dispersing at a stirring speed of 100-150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with double bonds on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11); S13) preparing a first polymer template emulsion, the specific steps are as follows: S13-1) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier in a weight ratio of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution; S13-2) By means of starvation polymerization, 0.4 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure; S14) preparing an emulsion containing organic nanoparticles, the specific steps are as follows: S14-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid, 3-butene-1-amine and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.1-1:0.01-0.02 to prepare a second mixed solution; S14-2) preparing a second polymer template emulsion: by means of starvation polymerization, 0.1 to 19 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 243 parts by weight of the first polymer template emulsion at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid-3-butene-1-amine) material containing an amino group is coated on the surface of the polyacrylamide latex particles to obtain a second polymer template emulsion having a multilayer core-shell structure; S14-3) preparing a third mixed solution: mixing ammonium polyphosphate, ethanol and deionized water in a weight ratio of 5-15:0.5-1:2-10 to prepare a third mixed solution; S14-4) preparing an emulsion containing organic nanoparticles: by means of an ion exchange reaction, 7 to 26 parts by weight of the third mixed solution are added dropwise to 41 to 302 parts by weight of the second polymer template emulsion at a constant speed at a temperature of 30 to 40° C., stirred at a stirring speed of less than 80 r / min, and refluxed and condensed for 4 hours under this temperature condition to form a polymer with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles, thereby obtaining an emulsion containing organic nanoparticles; S15) preparing an emulsion containing organic / inorganic hybrid nanoparticles, the specific steps are as follows: S15-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.01-0.02 to prepare a fourth mixed solution; S15-2) preparing a third polymer template emulsion: by means of a starvation polymerization method, at a temperature of 60 to 65° C., 0.1 to 18 parts by weight of the fourth mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having double bonds on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of the first polymer template emulsion at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silica particles having a particle size of 20 nm to 30 nm and having double bonds is coated on the surface of the polyacrylamide latex particles, thereby obtaining a third polymer template emulsion having a bayberry-like multilayer core-shell structure; S15-3) preparing a fifth mixed solution: preparing a fifth mixed solution by mixing glycidyl methacrylate, an initiator and deionized water in a weight ratio of 5-15:0.01-0.2:5-10; S15-4) preparing an emulsion containing organic / inorganic hybrid nanoparticles: adding 10 to 25 parts by weight of the fifth mixed solution to 51 to 327 parts by weight of the third polymer template emulsion at a constant speed at a temperature of 60 to 65° C., stirring at a stirring speed of less than 80 r / min, and reflux condensing for 3 hours at this temperature to form a second polymer with linear poly(glycidyl methacrylate) as a branch on the surface of the latex particles, thereby obtaining an emulsion containing organic / inorganic hybrid nanoparticles; S16) mixing the emulsion containing organic nanoparticles and the emulsion containing organic / inorganic hybrid nanoparticles to obtain a nanocomposite material.
7. A fire-proof pre-reaction liquid, characterized in that: The invention comprises at least the following components: 48 to 328 parts by weight of organic nanoparticles, 61 to 352 parts by weight of organic / inorganic hybrid nanoparticles, 0.5 to 4 parts by weight of cellulose solvent, 0.5 to 2.5 parts by weight of catalyst and 10 to 30 parts by weight of deionized water; the organic nanoparticles are the organic nanoparticles in the nanocomposite material described in claim 1, and the organic / inorganic hybrid nanoparticles are the organic / inorganic hybrid nanoparticles in the nanocomposite material described in claim 1.
8. The fire-proof pre-reaction liquid according to claim 7, characterized in that: The invention also comprises: 1 to 5 parts by weight of a carbonizing agent, 0.001 to 0.05 parts by weight of a defoaming agent and 0.1 to 1 parts by weight of a rheological aid; the carbonizing agent is compounded by pentaerythritol and one or more of sucrose, fructose, glucose and maltose; the rheological aid is one or more of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the antifreeze plasticizer is one or more of ethylene glycol, glycerol and 1,4-butanediol; the cellulose solvent is one or both of dipropylene glycol methyl ether and N-methyl morpholine oxide; the catalyst is compounded by a diluted hydrochloric acid solution with a mass concentration less than or equal to 20wt% and one or both of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite; the defoaming agent is one or both of a polysiloxane defoaming agent and a polyether defoaming agent.
9. The method for preparing the fire-proof pre-reaction liquid according to claim 8, characterized in that: The steps include: Step S21), a carbonizing agent, a rheological additive, and deionized water are mixed in a weight ratio of 1-5:0.1-1:10-25, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and allowed to stand for 12 hours to obtain a transparent and dynamically reversible gel material; Step S22) Organic nanoparticles, organic / inorganic hybrid nanoparticles, cellulose solvent, catalyst and deionized water are mixed in a weight ratio of 48-328:61-352:0.5-4:0.5-2.5:10-30 to obtain a first fire-proof mixed liquid, and stirred at a stirring speed of less than 80r / min at room temperature for 40 minutes to form a uniform suspension; 11-30 weight parts of gelling material are added to the first fire-proof mixed liquid, and stirred at a stirring speed of less than 80r / min at room temperature for 80 minutes to obtain a clear or slightly turbid second fire-proof mixed liquid; 0.5-2.5 weight parts of catalyst and 0.001-0.05 weight parts of defoaming agent are added to the second fire-proof mixed liquid in sequence, and stirred at a stirring speed of less than 80r / min at room temperature for 40 minutes to obtain a fire-proof pre-reaction liquid, which is allowed to stand for use.
10. The use of the fire-proof pre-reaction liquid according to claim 8, characterized in that: It is used for flame retardant treatment of transparent cellulose modified soda-lime glass products and forms a fireproof layer with a thickness of 0.02-0.3mm on the surface of the glass products. The specific operation is: spray the fireproof pre-reaction liquid onto the surface of the transparent cellulose modified soda-lime glass product, let it stand for 50 minutes, and after the surface of the glass product is dry, put it into a 50℃ oven for baking for 4 hours, and then heat it to 80℃ and bake for 3 hours, so that the cellulose on the glass surface and the fireproof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.
Citation Information
Patent Citations
Fireproof liquid of composite fireproof glass and preparation method thereof and composite fireproof glass
CN105131873A
Fireproof layer material, preparation method thereof, and fireproof glass
CN113929841A